Enhanced Nuclear State Density Equation in a Two-Component Pre-Equilibrium Exciton Model for Heavy Nuclei - Ahmed, Rasha S (Al-Nahrain Journal of Science, 2018)
The properties of nuclear state density which increases with increasing excitation energy are very important in many nuclear reactions. Previously, several theoretical calculations were performed and added to correct the state density equation. In this work, various corrections, i.e. the pairing effect, Pauli exclusion principle, parity, spin distribution, the finite depth and the bound state effect were added to enhance the state density results using the energy-dependent single-particle level densities (non-ESM) in 114Sn and 116Sn nuclei. The results of this work were compared to the available experimental (OSLO technique), and theoretical (E&B and HF-BCS) results. The calculations were performed for energies up to 80 MeV and show a reasonable match with experimental and theoretical results at low energies. At high energies the deformation effect affects the results and leads to mismatch between the results of this work and other results. The inclusion of the spin distribution function in case of j=1/(2 ), gives results far from the experimental data and previous theoretical results, which shows the importance of the introduction of a new formula that deals with a non-ESM system.